Workforce Planning for Oral Surgery and Oral and Maxillofacial Surgery in the United Kingdom: Aligning Future Service Provision With Patient Need - Adrian Thorp (Oral Surgery, 2026)
ABSTRACT Workforce pressures within United Kingdom Oral and Maxillofacial Surgery (OMFS) services include recruitment difficulties, consultant vacancies, increasing demand and concerns about the sustainability of emergency and specialist pathways. Although these challenges require action, workforce expansion should be based on population need, service activity, case mix and the competencies required to deliver care, rather than existing professional or organisational boundaries. This opinion article presents a critical narrative analysis of national policy, commissioning guidance and published workforce literature relating to Oral Surgery and OMFS. It considers the development of Oral Surgery as a distinct specialty, the distribution of secondary‐care activity, the contribution of Consultant Oral Surgeons, Oral Surgery specialists and SAS clinicians, and the evidence underpinning proposals for expansion of the dual‐qualified OMFS workforce. Available evidence indicates important gaps in national data concerning the case mix of hospital dental and maxillofacial services, the proportion of activity requiring dual‐qualified consultant care, and the professional groups delivering current services. A substantial component of secondary‐care demand relates to dentoalveolar and other core Oral Surgery activity. Failure to recognise this contribution may overestimate the requirement for one workforce group while underestimating existing and future Oral Surgery capacity. Integrated hub‐and‐spoke models and competency‐based workforce planning could support local access while protecting specialist OMFS capacity for trauma, oncology, reconstruction and complex craniofacial care. Future workforce planning should be founded on contemporary case‐mix, activity, outcome and competency data. Oral Surgery and OMFS should be developed as complementary components of an integrated service, with investment aligned to demonstrable patient need and clinicians enabled to work at the highest appropriate level of competence.